Histological Evaluation of Local Application of Flavonoid Extract of Capparis Spinosa on Wound Healing in Alloxan-Induced Diabetic Rats - Maryam Hameed Alwan; Ban A Ghani (Diyala Journal of Medicine, 2020)
Background: In diabetes, there are big concerns regarding impaired wound healing and other tissue disorders. The time and quality of wound healing are affected by many factors. One of the medical sciences ' aims is short-term wound healing with decreased side effects Herbal products are more valuable in both prophylaxis and curative in slowed diabetic wound healing as compared to synthetic drugs A considerable number of researches have shown that capers plant has distinct biological effects, including antioxidant, anticancer and antibacterial activity. Phytochemical analysis reveals C. Spinosa has large amounts of bioactive compounds, including polyphenolic compounds, which are essential for its health-promoting effects.